Factors Beyond the Language Barrier in Providing Health Care to Immigrant Patients - Fatahi, Nabi (Med Arch, 2016)
BACKGROUND: Due to the enormous migration as the result of war and disasters during the last decades, health systems in Europe are faced with various cultural traditions and both healthcare systems and healthcare professionals are challenged by human rights and values. In order to minimize difficulties in providing healthcare services to patients with different cultural backgrounds, cultural competence healthcare professionals are needed. MATERIAL AND METHODS: Four focus group interviews, were conducted with Kurdish immigrants in Scandinavian countries (N=26). The majority were males (n=18) aged between 33-61 years (M= 51.6 years) and a few were (n=8) females aged 41-63 years (M=50.7 years). The data were analyzed by using qualitative content analysis method. RESULTS: According to the study results participants experienced that diversities both in culture and healthcare routines create a number of difficulties regarding contact with healthcare services. Though culture related aspects influenced the process of all contact with health care services, the obstacles were more obvious in the case of psychological issues. The results of the study showed that cultural diversities were an obvious reason for immigrants’ attitudes regarding healthcare services in resettlement countries. CONCLUSION: The results of the study revealed a number of difficulties beyond linguistic problems regarding immigrants’ contact with healthcare services in Scandinavian countries. Problems were rooted both in diversities in healthcare services and cultural aspects. Immigrants’ views of healthcare systems and healthcare professionals’ approach in providing healthcare were some of the problems mentioned.